RANCANG BANGUN APLIKASI REKOMENDASI PENYALURAN TENAGA KERJA ALUMNI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SMK KETINTANG SURABAYA BERBASIS WEBSITE - prasetyo, Edy; Sulistiowati, Sulistiowati; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Â SMK Ketintang Surabaya is a private educational institution located on street Ketintang Surabaya. SMK Ketintang Surabaya has an institution called the Special Job Exchange (BKK) whose role is to optimize the distribution of SMK graduates and become a source of information for job seekers, namely students and SMK alumni. Currently the BKK institution is still having problems, namely the alumni data collection process is still manual, the submission of job vacancies information in vocational schools is still applying the conventional method, besides that if there is a demand for labor needed by the company the BKK section still finds difficulties when searching for workers according to the company's needs This is because alumni who apply to companies have inappropriate expertise competencies. Based on these problems, to help solve the problems that occur in BKK, it is necessary to apply a recommendation for the distribution of alumni workforce at SMK Ketintang Surabaya with the Simple Additive Weighting (SAW) method. The SAW method is used to provide recommendations to companies for alumni who have expertise competencies in accordance with job vacancies.